Islamic Studies in Indonesian Higher Education: Challenges and Opportunities for Interdisciplinary Approaches - Ali Mufron; Roya Zahir; Safiullah Aziz (Journal of Noesantara Islamic Studies, 2025)
Islamic Studies programs in Indonesian higher education have traditionally been rooted in classical, discipline-specific methodologies, which face challenges in addressing complex contemporary issues. This study aimed to identify and analyze the primary challenges and emerging opportunities for integrating interdisciplinary approaches within this field. A qualitative, multi-site case study methodology was employed, focusing on leading Islamic universities in Indonesia. Data were collected through curriculum analysis, policy document review, and in-depth interviews with faculty, academic leaders, and students. The results indicate that significant challenges persist, including institutional rigidity, disciplinary silos, and a faculty trained in mono-disciplinary traditions. However, substantial opportunities are emerging, driven by new government accreditation standards that favor interdisciplinarity and growing student demand for programs that connect Islamic sciences with social sciences, technology, and humanities. The study concludes that while structural and paradigmatic hurdles are significant, the push for interdisciplinary approaches presents a critical opportunity to revitalize Islamic Studies, enhancing its relevance and intellectual contribution to addressing modern societal challenges.